A comparison of the Hand Test results of Finnish and Lithuanian school children - Bliumas, Remigijus; Windgren, Marketta (Psichologija, 2000)
Although the Hand Test (HT) scores should be cautiously approached when using individuals from different cultures, the quantitative results of Finnish and Lithuanian groups of 13 year old children seem to be in line with Stetson’s and Wagner’s (1980) hypothesis on potential use of HT in different crosscultural studies. Finnish children scored higher on Exhibition, Active, Tension, Fear subcategories, on Environmental and Maladjustive combined categories, also on Total Number of Responses and Average initial Response Time. Lithuanian children scored higher on Description subcategory. The differences were more marked between the Finnish and Lithuanian girls than between the boys of these nations. The results are fixed as a starting point for /ong-term cross-cultural research.